The effect of R&D capitalization on revenue-expense matching: Focusing on the bio-pharmaceutical industries in South Korea - Dongjoon Choi; Inkyung Yoon; Hansol Lee (Investment Management & Financial Innovations)
The study aims to investigate the effect of research and development (R&D) capitalization on revenue-expense matching in the pharmaceutical and biotechnology industries, with particular attention to the moderating role of corporate governance and the influence of regulatory intervention. While capitalizing R&D expenditures enhances the relevance of financial information and positively impacts firm value, it also increases the risk of earnings management, potentially disrupting revenue-expense matching. Using a fixed-effects regression model, this study analyzes 1,350 firm-year observations from Korean listed firms in the bio-pharmaceutical sector from 2012 to 2022. The sample includes firms with financial statements, auditor data, and detailed disclosures on R&D expenditures, encompassing capitalized R&D costs, R&D expenses recognized in income statements, and those classified as manufacturing costs. The results indicate that R&D capitalization generally weakens revenue-expense matching in these industries. However, the adverse effects are mitigated by the effective implementation of corporate governance mechanisms. Additionally, the Financial Supervisory Service’s thematic supervision of R&D accounting practices has significantly improved revenue-expense matching. Prior to the supervision period (2012–2017), firms exhibited significant discretionary capitalization practices, undermining revenue-expense matching. Following the supervision (2018–2022), improved adherence to accounting standards has enhanced matching quality, underscoring the regulatory intervention’s effectiveness. These findings contribute to the literature by demonstrating that while discretionary R&D capitalization can impair revenue-expense alignment, strong corporate governance and adherence to accounting standards can offset these negative effects. The study provides valuable implications for future research and industry practices, particularly in navigating the trade-offs associated with R&D capitalization. AcknowledgmentThis study was supported by Chungnam National University.